Effects of chemical and bio-fertilizers on selected growth attributes of ‘bg 250’ rice (Oryza sativa l.) Cultivar - Rifnas, L.M.; Mahendran, S.; Iqbal, Y.B. (University of Jaffna, 2018)
Heavy usage of chemical fertilizers creates varieties of economic, environmental and ecological problems. Bio-fertilizers are one of the alternative means which include beneficial microorganisms to reduce harmful effects to human and environment. Considering this an experiment was conducted at the Rice Research Station, Sammanthurai, Sri Lanka in the ‘Yala’ 2017 to assess the effects of chemical and bio-fertilizers on plant height, Leaf Area Index, chlorophylls a, b and total chlorophyll contents and yield of rice cultivar ‘Bg 250’. The treatments were T1 - No fertilizer (Control), T2- 100% Recommended chemical fertilizer, T3-50% Chemical fertilizer + 50% Bio-fertilizer, T4-50% Bio fertilizer, T5-100% Bio-fertilizer. Bio-fertilizer consisted of Azotobacter chrocooccum, Azospirillum brasilense, Bacillus polymyxa, Bacillus megaterium and other Bacillus spp. in liquid based medium. The experiment was laid out in the Randomized Complete Block Design with five treatments and four replications. The application of chemical and bio-fertilizers has significantly (p<0.05) affected the tested growth parameters and yield of ‘Bg 250’ rice cultivar. The combined application of 50% chemical and 50% bio-fertilizer has given the highest plant height (58.2cm), the highest Leaf Area Index (2.5), the highest chlorophyll contents (Chl. a - 1.7 mgg-1, Chl. b-1.4 mgg-1 and total Chl. - 3.1 mgg-1) and yield (2500 kgha-1) compared to the other treatments. The control treatment where no fertilizers were added showed the lowest growth attributes and yield. Based on these results it was concluded that the combined application of 50% chemical and 50% bio-fertilizers has produced the highest growth performance and yield in the rice cultivar ‘Bg 250’. It could therefore be stated that bio-fertilizer in combination with chemical fertilizer could be used as an alternative way in the production of rice to boost the yield with reduced hazards to human health and environment.
Keywords: Bg 250; Bio-fertilizer; Chlorophyll content; Leaf area index; Plant height; Yield